Gender differences in defense mechanisms, ways of coping with stress and sense of identity in adolescent suicide attempts - Foto-Özdemir, Dilşad; Akdemir, Devrim; Çuhadaroğlu-Çetin, Füsun (The Turkish Journal of Pediatrics, 2016)
The main aim of this study was to investigate the gender differences in defense mechanisms, ways of coping with stress and identity formation in relation to adolescent suicidal behavior. This study involved 64 adolescents between 12-17 years of age, who were admitted to the emergency service with a suicide attempt. They were evaluated with a semi-structured clinical interview (K-SADS), Ways of Coping Inventory (WCI), Defense Mechanisms Inventory (DMI) and Sense of Identity Assessment Form (SIAF). 60.9% (n = 39) of the adolescents were female, and 39.1% (n=25) were male. There were no statistically significant differences between the girls and the boys with respect to the clinical characteristics of the suicide attempt and the rate of psychiatric disorders. Of the 64 adolescents with suicide attempt, 47 (73.4%) had at least one, and 26 (40.6%) had more than one psychiatric disorder according to K-SADS. Disruptive behavior disorders were more frequent in males, whereas depression was more frequent in girls. The data indicated the importance of identity confusion, major depression and ADHD in adolescents with suicide attempt in both genders. 43.6% (n=17) of the girls and 36% (n=9) of the boys obtained scores higher than the cut-off point of SIAF indicating identity confusion. Professional help seeking and NSSI behaviors before the suicide attempt were more common in adolescents with identity confusion. While there were differences between genders with respect to the defense mechanisms used, no significant difference was found in terms of ways of coping. Evaluation of DMI scores revealed that the turning against object subscale score was significantly higher in boys compared to girls. While evaluating the adolescents at risk, their defense mechanisms, way of coping and sense of identity, as well as their psychiatric diagnosis should be assessed in detail in order to identify the suicidal thoughts and prevent possible suicide attempts.
Keywords: adolescent; defense mechanism; gender; sense of identity; suicidal behavior; ways of coping